Penggunaan aplikasi “simulasi stail berfikir dan menyelesaikan masalah” dalam kalangan pelajar program pendidikan - Norshima, Azmi (2021)
Thinking styles are skills used to solve problems. Therefore, thinking styles and problem-solving skills have to be instilled among the education programme students in preparing them for their work place. However, there is still no application that has been built based on case simulations to stimulate thinking styles and problem-solving among students of education programme. This study aimed to investigate the effectiveness of the “Thinking Styles and Problem-Solving Simulation” application among the education programme students of Universiti Utara Malaysia. The ADDIE model was used to develop the application while the development of the case-based learning was based on Sternberg’s Mental Self-government and the 11 principles of Clyde Freeman Herreid theories. This study used the quasi-experimental pre-test post-test control group design and the explanatory sequential mixed-method design. The sample involved 70 education programme students who were selected through purposeful sampling and divided into the control group (n = 35) and the treatment group (n = 35). The instruments used in the pre-tests and the post-tests were the Thinking Style Inventory, the Problem Solving Inventory and the Motivated Strategies for Learning Questionnaire, expert’s and student’s evaluation questionnaires, activity checklists and interview protocols. The effectiveness of this interactive application was measured by comparing the pre-tests and post-tests scores of the treatment and control groups using the Multivariate Analysis of Covariance (MANCOVA) method. The results showed significant differences between the control and the treatment groups in thinking styles [F (13.43) = 4.90, p <.05], problem solving [F (3,63) = 3.96, p <.05] and self-regulated learning [F (5,59) = 9.0, p <.05]. The interview data revealed that this application was able to stimulate students’ thinking styles, problem-solving and self-regulation, via case-based learning. All students agreed that learning was enhanced by using the interactive application compared to the modular approach. The case-based learning application has successfully stimulated thinking styles, problem-solving skills and self-regulation among the education programme students.